Bag of bones - King, Stephen, 1947- (New York : Pocket Books, 1999)
Novelist Mike Noonan, still grieving the death of his wife after four years, retreats to Sara Laughs, his isolated summer home, but the peace he is seeking slips even further from his grasp when he finds the community in the grip of a powerful millionaire, and his hideaway becomes the site of ghostly visitations.
Library Journal.
Pub Weekly.
Wilson's Fiction.
Adult
Keywords: Vacation homes -- Maine -- Fiction; Widowers -- Fiction; Ghost stories; Vacation homes -- Fiction; Widowers -- Fiction; Maine -- Fiction; Maine -- Fiction